Bride price, dowry, and young men with time to kill: A commentary on men's marriage postponement in India. (2nd September 2022) - Basu, Alaka Malwade; Kumar, Sneha
Abstract : Rising numbers of young unmarried men in India reflect a marriage squeeze that goes beyond the shortage of brides created by sex-selective abortion. We describe a decline in men's marriageability caused by their falling economic prospects at the same time as families of brides are increasingly seeking grooms with stable employment. We group young men into those without jobs or much education, those with education but no work, and the privileged few with education as well as employment. This classification resolves some of the seeming contradictions in the qualitative literature on marriage in India. Some of this literature talks about the rising prevalence of bride price and some about the persistence of dowry, while some papers reflect in general on the costs of being young, male, and aimless. Our commentary includes a review of the growing literature on the physiological and (perhaps) consequently behavioural and health outcomes of men's anomie.